Disclosure of information about sustainable development in corporate reporting during martial status: the environmental aspect - Polishchuk, I.R.; Pylypchuk, A.O. (Problems of Theory and Methodology of Accounting, Control and Analysis, 2025)
The judicial practice regarding the completeness and timeliness of the assessment and payment of the environmental tax for 2020–2024 was analyzed. Typical violations in the assessment of environmental tax, which are systematic and deliberate in nature and lead to legal disputes regarding the collection of tax debt, have been established. Based on the analysis of the structure of paid environmental taxes in Ukraine, it was found that the largest source of damage caused by the activities of enterprises is emissions into the atmospheric air, and the smallest one is the pollution of water resources. The comparative characteristics of 10 enterprises according to various types of economic activity according to indicators of environmental responsibility are given. It was established that there is no single approach to disclosing the impact of the activities of the studied enterprises on the environment, which confirms the cause-and-effect relationship between industry specifics and the published absolute and relative indicators characterizing environmental responsibility. An algorithm for determining the productivity of costs for environmental protection measures has been developed. If, after the environmental protection measures have been implemented, water, energy, and fuel resources have been saved in the course of business processes, and the quality of products has not deteriorated, the amount of waste and emissions and discharges have not increased, then the costs of environmental protection measures are productive. The absolute and relative indicators of environmental responsibility in the Report on the management of the investigated 10 enterprises under different KVEDs are grouped according to the following directions: volumes of waste in natural terms; expenses for environmental protection measures; natural indicators regarding commissioned objects of nature protection importance; specific weight of energy sources that were used to produce electricity; volumes of water, gas, electricity use; the number of facilities with refrigeration equipment with a carbon dioxide cooler; volumes of renewal of fixed assets; natural indicators on the amount of savings due to trade without printing checks; expenses for environmental taxes; rent for the use of subsoil.